Biodegradable and Dual‐Responsive Polypeptide‐Shelled Cyclodextrin‐Containers for Intracellular Delivery of Membrane‐Impermeable Cargo (Adv. Sci. 18/2021). Issue 18 (22nd September 2021) - Kudruk, Sergej; Pottanam Chali, Sharafudheen; Linard Matos, Anna Livia; Bourque, Cole; Dunker, Clara; Gatsogiannis, Christos; Ravoo, Bart Jan; Gerke, Volker
Abstract : Dual‐Responsive Nanocontainers In article number 2100694, Bart Jan Ravoo, Volker Gerke, and co‐workers design nanocontainers based on cyclodextrin amphiphiles that are stabilized by a peptide shell and a redox‐responsive crosslinker. These dual‐responsive nanocontainers represent an efficient, biodegradable, and tunable system for overcoming the plasma membrane as a natural barrier for membrane‐impermeable cargo. The design was conceived by Sergej Kudruk and composed by Nina Knubel at the University of Münster.